Potential of Breadfruit Leaf Extract (Artocarpus altilis) As Functional Beverage for Patients with Hepatitis: Potensi Sirup Ekstrak Daun Sukun (Artocarpus altilis)Sebagai Minuman Fungsional Bagi Penderita Penyakit Hepatitis - Sarlina Palimbong; Gelora Mangalik; Agustina Basompe (Jurnal Sains dan Kesehatan, 2020)
Breadfruit leaves (Artocarpus altilis) are often used as ingredients of traditional medicine for treatment so it is recommended as a natural alternative medicine for patients with liver disease such as hepatitis. The purpose of this study is the use of breadfruit leaf extract for making syrup as a functional drink for people with hepatitis and see the panelists acceptance of the products made. Tests carried out were tests of the total content of flavonoid compounds and sensory tests on breadfruit leaf syrup. The results showed the highest total content of flavonoid compounds found in the leaves of breadfruit syrup PM (warming) 60 minutes amounted to 290.00 µgQe/mL and PM 90 amounted to 263.33 µgQe/mL while the lowest for the breadfruit leaf syrup PM 30 amounted to 240.00 µgQe/mL. The flavonoid content of all treatments showed a high amount. Based on a sensory test, the panelists preferred the syrup leaves of breadfruit PM 90 with average of 7.01. Therefore, of the three roots, PM 90 was the treatment recommendation. But to know the healing effect more than the consumption of flavonoids in syrup breadfruit leaves against hepatitis patients need to be tested in vivo.